Exploring agrifood value chains in India: Addressing subnational disparities at ICAE Symposium - CGIAR (CGIAR, 2024)
IFPRI organized a symposium titled “Agrifood Value Chains in India – Subnational Disparities and Priorities” at the 32nd International Conference of Agricultural Economists (ICAE) on 4th August under the CGIAR Initiatives on National Policies and Strategies (NPS) and Foresight. The panelists and participants discussed methodological, structural and policy-related issues on agrifood system transformation in India at the national and sub-national levels.